Effects of Image Upload on Social Media as Media Promotion in Journal Publishers - Untung Rahardja; Ani Wulandari; Marviola Hardini (CCIT Journal, 2020)
Digital content is content in various formats, whether written, image, video, audio or combination so that it can be read, displayed or played by a computer and easily sent or hared through digital media. Digital content has abundant benefits, especially in the field of promotion. Where when a place of business or a body wants to introduce a product or service that is owned, it definitely requires content such as images as a promotional media. However, if you have to distribute posters to everyone you meet, it is not in line with current technological advancements because you are still using a conventional process. Therefore, to overcome this problem, social media can be used to process digital content easily and quickly. In this study, there are 3 (three) problems that will be overcome by 2 (two) methods, and 3 (three) solutions are produced. The advantage of digital content in social media is that it can be accessed anytime and anywhere, so it is concluded that the use of digital content in social media is able to overcome problems and is a creativepreneur effort found in the promotion system of a journal publisher. Keywords—Digital Content, Creativepreneur, ATT Journal, Social Media